Definisi Konseptual E-Government dan E-Governance : Analisis Komparatif - Fauzi, Erinda Alfiani; Purnamawati, Nike (Wacana: Jurnal Ilmu Sosial dan Ilmu Politik Interdisiplin, 2025)
This research examines the conceptual distinctions between e-government and e-governance through comprehensive literature analysis. Although these terms are often used interchangeably, there are fundamental differences in their conceptual foundations, scope, and practical implications. The findings reveal that e-government tends to focus on technical and administrative aspects of technology implementation in government, while e-governance encompasses a broader perspective on the transformation of relationships between government, citizens, and other stakeholders. This research proposes an integrated conceptual framework that positions both concepts along a continuum of digital government development. The findings provide necessary conceptual clarification for theoretical development and practical implementation in the field of digital public administration, while encouraging a more holistic approach to understanding digital government transformation.